Exogenous cognition and cognitive state theory: The plexus of consumer analytics and decision-making. (March 2021) - Smith, Andrew; Harvey, John; Goulding, James; Smith, Gavin; Sparks, Leigh
We develop the concept of exogenous cognition (ExC) as a specific manifestation of an external cognitive system. ExC describes the technological and algorithmic extension of (and annexation of) cognition in a consumption context. ExC provides a framework to enhance the understanding of the impact of pervasive computing and smart technology on consumer decision-making and the behavioural impacts of consumer analytics. To this end, the article provides commentary and structures to outline the impact of ExC and to elaborate the definition and reach of ExC. The logic of ExC culminates in a theory of cognitive states comprising of three potential decision states: endogenous cognition, symbiotic cognition and surrogate cognition . These states are posited as transient (consumers might move between them during a purchase episode) and determined by individual propensities and situational antecedents. The article latterly provides various potential empirical avenues and issues for consideration and debate.